SAT0484 Bsmi VDR Gene Polymorphism is Associated with Bone Mineral Density and Bone Metabolism in Established Rheumatoid Arthritis Patients. (10th June 2014) - Bernardes, M.; Machado, J.C.; Vieira, T.; Gonçalves, D.; Vieira, R.; Fonseca, R.; Madureira, P.; Abelha-Aleixo, J.; Bernardo, A.; Pereira, J.G.; Martins, M.J.; Costa, L.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is characterized by a localized bone resorption at the hands, namely, as well as a generalized osteoporosis. BsmI vitamin D receptor (VDR) gene polymorphism is a well known genetic determinant of bone mineral density (BMD) in healthy populations. Objectives: Determine the degree of association of BsmI VDR gene polymorphism with BMD and bone metabolism in patients with established RA. Methods: Clinical features and peripheral blood samples were collected from a monitoring visit. HAQ and DAS28 (4v) were obtained. We measured the following laboratory parameters: ESR, CRP, serum β-CTX1, osteocalcin, Dkk-1, sclerostin, RANKL and OPG. Genomic DNA was extracted from blood and genotyped for the BsmI (A/G) (rs1544410) SNP by PCR-RFLPs analysis. BMD was assessed by Dual energy X-ray Absorptiometry (Lunar Expert ® 1320) at the lumbar spine, total hip, femoral neck, hands and second proximal phalanges. A multivariate analysis model was used for statistical analysis (IBM SPSS Statistics 21). Results: We evaluated 208 RA patients, 166 (80%) women, 65 (31%) premenopausal women, age 54±12 years, disease duration 14±10 years, mean DAS28 (4v) of 4.25±1.33 and a mean HAQ of 1.254±0.709. In our sample, 107 (51%) were under biologics, 87 (42%) under anti-TNFalpha agents, 69 (33%) under bisphosphonates and 42 (20%) under vitamin D supplements, Genotype frequencies were determined for BsmI VDR gene polymorphism: GG 37%, AG 44%, AA 19%. AA genotype was associated with higher BMD at femoral neck, lumbar spine, hands and second proximal phalanges (p<0.001). In the subgroup of patients without vitamin D supplements, AA genotype was also associated with higher BMD at the hip (p<0.001). These associations were found after adjusting for age, disease duration, body mass index, DAS28 (4v), current HAQ, time under DMARDs therapy, years of corticosteroid use and years of bisphosphonates use. In terms of bone metabolism, AA genotype was associated with higher values of Dkk-1 (p<0.05) and sclerostin (p<0.001). The presence of A allele was associated with higher RANKL levels (p<0.05). In the subgroup of patients without vitamin D supplements, AA genotype was only associated with higher sclerostin levels (p<0.001). These later associations were found after adjusting for age, age at diagnosis, disease duration, body mass index, DAS28 (4v), current HAQ, current average daily dose of prednisolone and years of bisphosphonates use. Conclusions: BsmI VDR gene polymorphism may serve as a genetic marker of both, localized and generalized, bone loss in RA population since it is associated with BMD in several anatomic sites. The link of this polymorphism to high serum levels of sclerostin reinforce a possible role for this bone marker in coupling bone resorption to bone formation. There is recent evidence that zoledronic acid increases sclerostin serum levels in treated postmenopausal women and that sclerostin serum levels correlate positively with BMD in haemodialysis patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3868